METHODS FOR PRESERVATION THE PATENCY OF THE INTERNAL ILIAC ARTERIES DURING INFRARENAL AORTIC ANEURISM RESECTION - N. A. Yaitsky (Вестник хирургии имени И.И. Грекова, 2018)
OBJECTIVE. The purpose of this study was to evaluate the methods for preservation the patency of the internal iliac arteries during infrarenal aortic aneurysm resection.MATERIAL AND METHODS. The retrospective review was conducted in 200 patients who had undergone infrarenal aortic aneurysms resection between 1998 and 2017. The group 1 consisted of 8 patients who underwent the antegrade internal iliac arteries flow restoration by bypass or prosthetics. The group 2 consisted of 25 people who did not undergo restorating the patency of these arteries. The results were compared in both groups during the intraand early postoperative period.RESULTS. During the statistical analysis, there were no significant differences in duration of operation postoperative period, blood loss between two groups. Among the patients of the group 2, a transient ischemic colitis developed in one case, a prosthesis thrombosis developed in 5 patients. The complications described above have never been noted in the group 1.CONCLUSION. Direct revascularization of the internal iliac arteries during infrarenal aortic aneurism resection is an important factor of preventing the ischemic disorders of the pelvic organs and the left half of the colon do not significantly affect the volume of blood loss and the duration of the operation and the postoperative period.